Understanding Higher Education in Canada as a Human Right - Danielle Milln (Canadian Society for Studies in Education, 2021)
Education is well-established by the United Nations (1948) as a fundamental human right, though there is a paucity of literature specifically surrounding higher education as a human right. Financial access to post-secondary education is a growing issue in Canada as provincial governments implement neoliberal policies that increasingly privatize higher education, passing the burden of affordability to students. This paper explores Canada's commitment to higher education as a human right through international human rights law and examines neoliberal policies preventing the equitable realization of this right through case studies of Ontario and Alberta while recommending a reimagined system of PSE management to ensure equitable and inclusive participation in PSE throughout Canada.